INDONESIA'S EFFORTS IN ACCELERATING CARBON NEUTRALITY TARGETS POST G20 BALI SUMMIT - Soulthanarafif, Teuku M.; Iqbal, M. Putra; Farsia, Lena (Zhata Institut, 2025)
The G20 is an international cooperation forum consisting of 20 countries with the world's largest economies, responsible for approximately 75% of global greenhouse gas emissions. Due to extensive use of carbon-based fuels, there has been a worrisome rise in global temperatures. The non-binding nature of decision-making within the G20 as an international cooperation forum poses a challenge to accelerating the achievement of Carbon Neutrality targets. This article discusses how G20 summits influence the acceleration of Carbon Neutrality targets and Indonesia's legal steps towards achieving them. The normative legal research method is applied to explain various legal concepts and principles relevant to this article. The research highlights the connection between the G20 and achieving Carbon Neutrality targets, emphasizing strong encouragement for member states, exemplified by the emergence of the Bali Common Principle in Accelerating Clean Energy Transition (Bali COMPACT) and its principles for expediting environmentally friendly energy transitions. The Indonesian government's commitment to transitioning to clean energy is reflected in regulations such as Presidential Regulation No. 112 of 2022 and the discussion of the Renewable Energy Bill (RUU EBT).